Suction Monitoring and Stability of Volcanic-Residual Soil Slope during Rainfall - Agus Setyo Muntohar; Nurul Fata; Apiniti Jotisankasa; Kuo-Hsin Yang (Civil Engineering Dimension, 2020)
Some slopes in Yogyakarta, Indonesia, were covered by volcanic soil of the quaternary deposit of Merapi volcano. Typically, the soil layers of the slope consist of fine sand or silty sand. During the wet season (November – February), the slope is prone to instability due to rainfall infiltration. This paper presents the field suction monitoring of silty-sand slope. A 2.57 m high slope at Universitas Muhammadiyah Yogyakarta campus was instrumented with a mini tensiometer, moisture probe, and rain gauge to study the effect of suction on the slope stability during rainfall in wet season. The investigation shows that the rainfall decreases the suction and increase the moisture of soil. This situation leads to slope instability. The factor of safety fluctuates corresponding to the rainfall intensity. The lowest factor of safety was attained on 30 December, in which the rainfall intensity is the highest, i.e. 48 mm/day.